1991
DOI: 10.1523/jneurosci.11-07-02226.1991
|View full text |Cite
|
Sign up to set email alerts
|

Halothane inhibits two components of calcium current in clonal (GH3) pituitary cells

Abstract: The effect of halothane on isolated calcium (Ca2+) current of clonal (GH3) pituitary cells was investigated using standard whole-cell clamp techniques at room temperature. Halothane (0.1–5.0 mM) reversibly reduced both the low-threshold, transient [low-voltage-activated (LVA)] component and the high-threshold [high-voltage-activated (HVA)] component of Ca2+ current. Halothane had little effect on the voltage dependence of activation or inactivation of either component of Ca2+ current. Inhibition of the peak hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…see Terrar & Victory, 1988) and recent evidence shows that the L-and T-type currents of cardiac Purkinje fibres are affected by halogenated volatile anaesthetics to an approximately equal extent (Eskinder, Rusch, Supan, Kampine & Bosnjak, 1991). In clonal pituitary cells (GH3 cells) the lowthreshold current was resistant to halothane, while highthreshold calcium current was strongly inhibited (Herrington, Stern, Evers & Lingle, 1991). In this study the sustained component showed greater sensitivity than the inactivating current, possibly reflecting a greater sensitivity of L-type calcium channels.…”
Section: Discussionsupporting
confidence: 45%
“…see Terrar & Victory, 1988) and recent evidence shows that the L-and T-type currents of cardiac Purkinje fibres are affected by halogenated volatile anaesthetics to an approximately equal extent (Eskinder, Rusch, Supan, Kampine & Bosnjak, 1991). In clonal pituitary cells (GH3 cells) the lowthreshold current was resistant to halothane, while highthreshold calcium current was strongly inhibited (Herrington, Stern, Evers & Lingle, 1991). In this study the sustained component showed greater sensitivity than the inactivating current, possibly reflecting a greater sensitivity of L-type calcium channels.…”
Section: Discussionsupporting
confidence: 45%
“…Both isoflurane and halothane block T-type currents at therapeutically relevant concentrations of anesthetics (50). Block of high voltage-activated currents by halothane occurs at similar millimolar concentrations (51,52).…”
Section: Anestheticsmentioning
confidence: 99%
“…Serotonin (5-HT3) receptors exhibit both inhibition and activation, which depends on the molecular volume of the anesthetic (6, 7, 16 -21). The interactions of voltage-gated ion channels with inhaled anesthetics are less well characterized and, to the best of our knowledge, the available studies of these targets report only inhibition by inhaled anesthetics (10,(22)(23)(24)(25)(26)(27)(28)(29). Previously, we characterized the inhibition of the archetypical Drosophila voltage-gated K ϩ (Kv) channel K-Shaw2 (a Kv3 homolog) by relevant concentrations of n-alcohols and inhaled anesthetics (12, 30 -33).…”
mentioning
confidence: 99%